2019
DOI: 10.3847/1538-4357/ab3392
|View full text |Cite
|
Sign up to set email alerts
|

Large Molecular Gas Reservoirs in Star-forming Cluster Galaxies

Abstract: We present CO(2-1) observations of 72 galaxies in the nearby, disturbed Antlia galaxy cluster with the Atacama Pathfinder Experiment (APEX) telescope. The galaxies in our sample are selected to span a wide range of stellar masses (10 8 M M 10 10 M ) and star formation rates (0.0005 M yr −1 < SFR < 0.3 M yr −1 ). Reaching a depth of 23 mJy in 50 km s −1 channels, we report a total CO detection rate of 37.5% and a CO detection rate of 86% for sources within 1 dex of the main sequence. We compare our sample with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 128 publications
0
10
0
Order By: Relevance
“…This could be also attributed to the bar-driven enhancement of star formation. However, in non-interacting clusters, the bar formation is 17 Several previous studies show that some galaxies in clusters in merging processes or with substructures can have large amounts of H I gas or molecular gas contents that are comparable to field galaxies Cybulski et al 2016;Cairns et al 2019). likely not due to a cluster-wide mechanism occurring in a narrow time period as in the case of interacting clusters. Therefore, a number of bars formed recently (and subsequent star-formation activities triggered recently) would be smaller in non-interacting clusters than in interacting clusters.…”
Section: Normalized Countmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be also attributed to the bar-driven enhancement of star formation. However, in non-interacting clusters, the bar formation is 17 Several previous studies show that some galaxies in clusters in merging processes or with substructures can have large amounts of H I gas or molecular gas contents that are comparable to field galaxies Cybulski et al 2016;Cairns et al 2019). likely not due to a cluster-wide mechanism occurring in a narrow time period as in the case of interacting clusters. Therefore, a number of bars formed recently (and subsequent star-formation activities triggered recently) would be smaller in non-interacting clusters than in interacting clusters.…”
Section: Normalized Countmentioning
confidence: 99%
“…This could be also attributed to the bar-driven enhancement of star formation. However, in non-interacting clusters, the bar formation is 17 Several previous studies show that some galaxies in clusters in merging processes or with substructures can have large amounts of H I gas or molecular gas contents that are comparable to field galaxies (Stroe et al 2015;Cybulski et al 2016;Cairns et al 2019).…”
Section: Table 1 Total Number Of Galaxies In Each Categorymentioning
confidence: 99%
“…Cohen et al 2014;Yoon & Im 2020) and blue galaxies (e.g. Wang et al 1997;Cortese et al 2004;Hou et al 2012;Cava et al 2017) and are more gas-rich than counterparts in relaxed clusters (Stroe et al 2015a;Jaffé et al 2012Jaffé et al , 2016Cairns et al 2019). There is also compelling evidence from multiwavelength data that cluster mergers trigger AGN activity (Miller & Owen 2003;Owen et al 1999;Sobral et al 2015;Hwang & Lee 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Andrade-Santos et al 2017;Rossetti et al 2017) and of particular interest to the community as they present some surprising reversals of the typical environmental trends found in relaxed clusters. Studies contrasting statistical samples of relaxed and merging clusters, found that merging galaxy clusters have a higher density of emission-line, star-forming and blue galaxies, with higher specific SF rates (sSFR), stronger barred morphological features and large gas reservoirs and a higher fraction of active galactic nuclei (AGN) (Miller & Owen 2003;Cortese et al 2004;Hwang & Lee 2009;Hou et al 2012;Jaffé et al 2012Jaffé et al , 2016Sobral et al 2015;Stroe et al 2015b,a;Stroe et al 2017;Cairns et al 2019;Yoon et al 2019;Yoon & Im 2020).…”
Section: Introductionmentioning
confidence: 99%